1981
DOI: 10.1093/nar/9.24.6953
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the yeast ribosomal RNA genes. 4. Complete sequence of the 25 S rRNA gene from Saccharomyces cerevisiae

Abstract: The complete nucleotide sequence of the 25 S rRNA gene from one rDNA repeating unit of Saccharomyces cerevisiae has been determined. The corresponding 25 S rRNA molecule contains 3392 nucleotides and has an estimated relative molecular mass (Mr, Na-salt) or 1.17 x 10(6). Striking sequence homology is observed with known 5'- and 3'-end terminal segments of L-rRNA from other eukaryotes. Possible models of interaction with 5.8 S rRNA are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(103 citation statements)
references
References 23 publications
2
100
0
Order By: Relevance
“…The size of cytosol rRNAs in S . cerevisiae was identical to the published results (Georgiev et al, 1981;Rubtsov et al, 1980). Moreover, electrophoresis on glyoxal gels (Maniatis et al, 1982) also supported the above sizes (data not shown).…”
Section: Restriction Enzyme Analysissupporting
confidence: 90%
“…The size of cytosol rRNAs in S . cerevisiae was identical to the published results (Georgiev et al, 1981;Rubtsov et al, 1980). Moreover, electrophoresis on glyoxal gels (Maniatis et al, 1982) also supported the above sizes (data not shown).…”
Section: Restriction Enzyme Analysissupporting
confidence: 90%
“…Yamadazyma philogaea CBS 6696 was linked to the cluster of Debaryomyces species at 8 base differences. Torulaspora globosa IFO 1160 and S cerevisiae IFO 2376 constituted a (4). N, A, G, C, or U.…”
Section: Resultsmentioning
confidence: 99%
“…The partial base sequences of 18S and 26S rRNAs of the yeast strains were determined by the method of Lane et al (10) using reverse transcriptase. The oligonucleotide DNA primers used in this experiment were 5'-ACGGGCGGTGTGTAC-3', which is complementary to the sequence of positions 1641 through 1627 of 18S rRNA (in Saccharomyces cerevisiae) (12) and 5'-GGTCCGTGTTTCAAGACGG-3' and 5'-TTGGAGACCTG-CTGCGG-3', which are complementary to the sequences of positions 654 through 636 and 1857 through 1841, respectively, of 26S rRNA (in S cerevisiae) (4).…”
Section: Methodsmentioning
confidence: 99%
“…The partial base sequences of 18S and 26S rRNAs of these yeast strains were determined by the methods of Lane (13,14). The oligonucleotide DNA primers used in this experiment were 5'-ACGGGCGGTGTGTAC-3', which is complementary to the sequence of positions 1641 through 1627 of 18S rRNA (in Saccharomyces cerevisiae) (6) and 5'-GGTCCGTGTTTCAAGACGG-3' and 5'-TTGGAGACCTGCTGCGG-3', which are complementary to the sequences of positions 654 through 636 and 1857 through 1841, respectively, of 26S rRNA (in S. cerevisiae) (2).…”
Section: Methodsmentioning
confidence: 99%